Process and materials for trim dewaxing of distillates
The use of coextruded zeolite catalysts with non-noble or noble metals in the dewaxing process addresses the challenge of high activity and selectivity in distillate dewaxing, enhancing cloud point reduction and diesel yield.
Patent Information
- Application Number
- JP2024154855
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-06-17
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing dewaxing processes for distillate boiling range feeds, particularly for diesel, face challenges in achieving high activity and selectivity while minimizing diesel loss, and there is a need for improved catalysts that enhance cloud point reduction.
A dewaxing process using a coextrudate catalyst composed of two different 10-ring framework zeolites or a combination of 10-ring and 12-ring framework zeolites, along with non-noble or noble metal components, to enhance activity and selectivity.
The coextruded zeolite catalysts demonstrate superior cloud point reduction and diesel yield compared to single zeolite components, achieving accelerated cloud point reduction with reduced diesel loss.
Smart Images

Figure 2025000661000004 
Figure 2025000661000005 
Figure 2025000661000006
Abstract
Description
[Technical field]
[0001] Related Applications This application claims the benefit of U.S. Provisional Patent Application No. 63 / 040,294, filed June 17, 2020, entitled "Process And Materials For Trim Dewaxing Of Distillates," the contents of which are incorporated herein by reference.
[0002] The present invention relates to a process and catalyst for the dewaxing of hydrocarbon distillate boiling range feeds, and particularly, but not exclusively, to such a process and catalyst for dewaxing distillate boiling range feeds suitable for diesel boiling range products. [Background technology]
[0003] In the last few decades, the increasing demand for diesel worldwide has forced refineries and third party users to face cold flow constraints in their production. To overcome these constraints, many refineries have been forced to blend kerosene or use additives to improve cold flow properties. These treatments are often not cost effective and are limited in their performance beyond a certain point where cold flow properties change.
[0004] One way to improve the cold flow properties of distillate feeds is through a dewaxing process. Dewaxing is an established process for treating petroleum fractions to remove hydrocarbons that tend to solidify, particularly straight and slightly branched chain waxy paraffins. Dewaxing can be carried out by solvent extraction and crystallization, but in the past few years there has been a focus on processes that remove wax by selective catalytic conversion of straight and slightly branched chain paraffins. In catalytic dewaxing processes, the waxy paraffins are (de)hydrogenated, cracked and / or isomerized to compounds that do not adversely affect the cold flow properties of the distillate product.
[0005] The key to an effective distillate catalytic dewaxing process is to isomerize these compounds without incurring yield losses due to (de)hydrogenation and / or cracking of the distillate to lighter products. The emerging application space for distillate dewaxing has been identified with trim sour service. These applications generally have in common the need for minor adjustments in the haze of the reaction product, typically in the range of 3-15°C. The proposed scenario calls for replacing a small portion of the hydrotreating catalyst, typically present in the bottom layer of the reactor, with an isomerization catalyst. The isomerization catalyst generally consists of an acidic component (usually a zeolite) and a metal component. The metal component functions to (de)hydrogenate paraffins to olefins, which are then isomerized by the acid. Traditionally, noble metals such as platinum have been preferred because of their suitability for (de)hydrogenation, but these materials typically suffer significant poisoning from the sulfur present in the distillate feed. Baser metals (e.g., non-noble metals) are more resistant to this type of poisoning, but are preferred for sour service because they are believed to have some hydrotreating activity. Achieving a balance between olefin production / (de)hydrogenation and olefin isomerization is crucial to formulating a catalyst with high activity and selectivity.
[0006] One example of such a process is disclosed in U.S. Patent No. 5,393,633, which discloses a process for dewaxing a hydrocarbon feedstock containing waxy components, which comprises contacting the feedstock under dewaxing conditions with a catalyst system comprising ZSM-48 and MTT framework type molecular sieves. The molecular sieves disclosed therein, ZSM-48 and ZSM-23, or combinations thereof, are selective for dewaxing by isomerization as opposed to cracking. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] U.S. Pat. No. 8,298,403 Summary of the Invention [Problem to be solved by the invention]
[0008] Despite these advances, there remains a need for improved trim dewaxing processes for distillate boiling range feeds and catalysts therefor, particularly those processes and catalysts that exhibit a combination of high activity for increased cloud point reduction and increased selectivity for reduced diesel losses. [Means for solving the problem]
[0009] It has now been found that a dewaxing process employing a dewaxing catalyst which is a co-extrudate of two different zeolites, particularly two different 10-membered ring framework (10MR) zeolites, or a 10MR and a 12-membered ring framework (12MR) zeolite, in combination with a mixture of non-precious metal components or precious metal components, meets these and other needs.
[0010] In one embodiment, a process for trim dewaxing a distillate boiling range feed is disclosed. The process employs a dewaxing catalyst that is a co-extrudate of two zeolites and employs a first and a second non-precious metal. The process may include contacting at least a portion of the distillate boiling range feed with the dewaxing catalyst under effective dewaxing conditions to form a diesel boiling range product. The dewaxing catalyst may include either (a) a co-extrudate of two different 10-ring framework (10MR) zeolites; or (b) a co-extrudate of one 10MR zeolite and one 12-ring framework (12MR) zeolite; and a non-precious metal component. The non-precious metal component may be a combination of multiple metals, such as (c) a first metal selected from the group consisting of nickel, cobalt, and mixtures thereof; and (b) a second metal selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof. In yet another aspect, another process for trim dewaxing a distillate boiling range feed is disclosed in which the dewaxing catalyst is also a co-extrudate of two zeolites, but now employing a precious metal. The process may include contacting at least a portion of the distillate boiling range feed with the dewaxing catalyst under effective dewaxing conditions to form a diesel boiling range product. The dewaxing catalyst may include (a) a co-extrudate of two different 10MR zeolites; or (b) a co-extrudate of a 10MR zeolite and a 12MR zeolite, and may optionally include one or more precious metals, such as (c) a precious metal selected from the group consisting of palladium, platinum, and mixtures thereof.
[0011] Advantageously, the 10MR zeolite may have a framework type selected from the group consisting of EUO, MEL, MFI, MFS, MRE, MTT, MWW, MWW, NES, TON, and mixtures thereof. The framework 10MR zeolites may be selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, ZSM-23, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof.
[0012] Advantageously, the 12MR zeolite is * The 12MR zeolites may have a framework type selected from the group consisting of BEA, BEC, EMT, FAU, LTL, MEI, MOR, MOZ, MTW, MSE, OFF, and mixtures thereof. These framework 12MR zeolites may be selected from the group consisting of beta, ZSM-2, ZSM-3, ZSM-20, Y, US-Y, L, ZSM-18, mordenite, ZSM-10, ZSM-12, MCM-68, offretite, and mixtures thereof.
[0013] In yet another aspect, a method for forming a dewaxing catalyst is provided. The method includes several steps. A mixture is formed that includes a first zeolite, a second zeolite, and a binder. The mixture is kneaded to form an extrudable paste, which is extruded to form extrudates, which are dried. The dried extrudates are impregnated with a solution that includes a source of Group 6 metal ions, a source of Group 10 metal ions, and optionally a dispersing agent to form metal-containing extrudates. The metal-containing extrudates are dried at a temperature of about 80° C. to about 200° C. to form a dewaxing catalyst. Optionally, the dewaxing catalyst is ion-exchanged with a source of ammonium ions, washed with water, dried, and calcined.
[0014] In yet another embodiment, a catalyst for trim dewaxing of a distillate boiling range feed is provided, which may be (a) a coextrudate of two different 10MR zeolites, or (b) a coextrudate of a 10MR zeolite and a 12MR zeolite, and, optionally, (c) a precious metal selected from the group consisting of palladium, platinum, and mixtures thereof.
[0015] Advantageously, the catalyst comprises at least one of: (a) ZSM-11, ZSM-48, nickel, and molybdenum; or (b) ZSM-48, ZSM-23, nickel, and molybdenum; or (c) ZSM-48, ZSM-12, nickel, and molybdenum. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 shows the cloud point lowering performance of materials containing MEL and MRE(10MR) frameworks over a temperature range.
[0017] [Diagram 2] FIG. 1 shows diesel loss versus cloud point reduction for materials containing MEL and MRE(10MR) backbones.
[0018] [Diagram 3] FIG. 1 shows the cloud point lowering performance of materials containing MTT and MRE(10MR) skeletons over a certain temperature range.
[0019] [Figure 4] FIG. 1 shows diesel loss versus cloud point reduction for materials containing MTT and MRE(10MR) backbones.
[0020] [Diagram 5] FIG. 1 shows the cloud point reduction performance of materials containing MTT and MRE(10MR) frameworks loaded with various metals over a certain temperature range.
[0021] [Figure 6]FIG. 1 shows diesel losses versus cloud point reduction for materials containing MTT and MRE(10MR) frameworks loaded with various metals.
[0022] [Figure 7] FIG. 1 shows the cloud point reduction performance of materials containing MTW (12MR backbone) and MRE (10MR) backbones over a temperature range.
[0023] [Figure 8] FIG. 1 shows diesel losses versus cloud point reduction for materials containing MTW (12MR) and materials containing MRE (10MR). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] overview Described herein is a novel, inventive dewaxing process that employs a dewaxing catalyst that is a co-extrudate of two different zeolites, specifically a co-extrudate of two different 10MR zeolites or a co-extrudate of a 10MR zeolite and a 12MR zeolite, in combination with a hydrogenation component that may be a mixture of non-precious metal components or a mixture of precious metal components. This novel, inventive process has demonstrated a significant activity boost (measured by accelerated cloud point reduction) and / or selectivity boost (measured by reduced diesel losses) compared to either a single zeolite component. Surprisingly, the co-extruded (co-extruded) material also exhibits higher activity and selectivity than a physical mixture of the separate zeolite components. The ability to accelerate cloud point reduction by co-extruding materials with metal components is shown across a range of zeolite frameworks, including co-extrusions of different 10MR frameworks, e.g., MRE, MEL, MTT; and even co-extrudates of such 10MR zeolites with 12MR zeolites, e.g., MTW, show accelerated cloud point reduction. These performance advantages for the co-extruded materials are also shown across a variety of feedstocks.
[0025] definition The term "framework type" as used herein has the meaning given in "Atlas of Zeolite Framework Types" (Ch. Baerlocher, W. M. Meier and D. H. Olson, Elsevier, 5th Ed., 2001).
[0026] As used herein, the term "zeolite" is used interchangeably with the term "molecular sieve."
[0027] As used herein, the term "Periodic Table" means the "IUPAC Periodic Table of the Elements" (dated May 1, 2013), which is shown on the inside cover of "The Merck Index, Twelfth Edition" (Merck & Co., Inc., 1996).
[0028] Distillate Feed Feedstocks (i.e., feed products) that can be dewaxed using the dewaxing catalyst of the present invention. Such feedstocks range from relatively light distillate fractions, such as kerosene and jet fuel, to higher boiling stocks, such as whole crude petroleum, reduced crudes, vacuum tower residue, cycle oil, synthetic crude oil (e.g., shale oil, tars and oil, etc.), gas oil, vacuum gas oil, foots oil, Fischer-Tropsch derived wax, and other heavy oils. Linear n-paraffins having 16 or more carbon atoms, either alone or in combination with slightly branched chain paraffins, are sometimes referred to as wax. The feedstocks are often C 2 O 4 , which generally have a boiling point above about 350° F. (177° C.). 10+The feedstocks will be the lighter oils, since they will not normally contain significant amounts of waxy components. However, the dewaxing catalyst is particularly useful for those whose pour points and viscosities need to be maintained within certain specification limits, such as: waxy oil stocks, such as middle distillate stocks (including gas oils, kerosene, and jet fuel), lube oil stocks, heating oils, and other distillate fractions. Lube oil stocks will generally boil above 230°C (450°F), more commonly above 315°C (600°F). Hydrotreated stocks are a convenient source of this type of stock, and also other distillate fractions, since they will usually contain significant amounts of waxy n-paraffins. The feedstocks will usually be C 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 10+ The feedstock is generally a crude oil, but contains substantial amounts of higher n-paraffins and slightly branched paraffins, which contribute to the waxy nature of the feedstock. In the process, the n-paraffins are isomerized to branched paraffins, but also undergo some cracking or hydrocracking to produce liquid range materials that contribute to the low viscosity reaction products. However, the extent of cracking that occurs is limited to reduce the yield of reaction products that have boiling points lower than that of the feedstock, thereby maintaining the economic value of the feedstock.
[0029] Dewaxing Catalyst In various embodiments, at least a portion of the dewaxing catalyst of the present invention comprises a co-extrudate of two different 10-ring zeolites and a non-precious metal hydrogenation component. The non-precious metal hydrogenation component comprises a first metal and a second metal. The first metal can be selected from the group consisting of nickel, cobalt, and mixtures thereof, preferably nickel or cobalt. The second metal can be selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof, preferably molybdenum and tungsten.
[0030] In another embodiment, at least a portion of the dewaxing catalyst of the present invention comprises a co-extrudate of a 10-ring zeolite and a 12-ring zeolite and a precious metal hydrogenation component, which may be selected from the group consisting of palladium, platinum, and mixtures thereof, preferably platinum.
[0031] Molecular sieves having a 10MR framework that are suitable for the dewaxing catalyst of the present invention include molecular sieves such as crystalline aluminosilicates (eg, zeolites).
[0032] In one or more embodiments, the 10MR framework may comprise, consist essentially of, or be a framework type selected from the group including, but not limited to, EUO, MEL, MFI, MFS, MRE, MTT, MWW, MWW, NES, TON, and mixtures thereof. Zeolites having such 10MR frameworks include, but are not limited to, ZSM-50, EU-1 (EUO), ZSM-11 (MEL), ZSM-5 (MFI), ZSM-57 (MFS), ZSM-48 (MRE), ZSM-23 (MTT), EMM-10, MCM-22, MCM-49, MCM-56 (MWW), NU-87 (NES), ZSM-22, Theta-1 (TON), and mixtures thereof. It should be noted that zeolites having a silica to alumina ratio of from about (20:1) to about (40:1) and having the ZSM-23 structure are sometimes also referred to as SSZ-32.
[0033] In one or more embodiments, the 12MR backbone is * The zeolite may comprise, consist essentially of, or be a framework type selected from the group including, but not limited to, BEA, BEC, EMT, FAU, LTL, MEI, MOR, MOZ, MTW, MSE, OFF, and mixtures thereof. Such zeolites having a 12MR include, but are not limited to, Beta (BEA and BEC), ZSM-2, ZSM-3, ZSM-20 (EMT), Y, US-Y (FAU), Zeolite L (LTL), ZSM-18 (MEI), Mordenite (MOR), ZSM-10 (MOZ), ZSM-12 (MTW), MCM-68 (MSE), Offretite (OFF), and mixtures thereof.
[0034] Optionally, one or, more preferably, both of the molecular sieves employed in the dewaxing catalyst and process of the present invention may be combined with other materials that are resistant to the temperature and other conditions employed in the dewaxing process. Such materials are also referred to as binder or matrix materials. Such binder or matrix materials include active and inactive materials, such as synthetic or naturally occurring zeolites, as well as inorganic materials, such as clays, silica, and / or metal oxides, such as alumina, titania, and / or zirconia. Preferably, the dewaxing catalyst (in bound form) has a zeolite to binder ratio, as the case may be, of at least about 1.2, e.g., at least about 2.0, at least about 4.0, or at least about 4.5, by weight.
[0035] The latter may be either naturally occurring or in the form of gelatinous precipitates, sols, or gels, including mixtures of silica and metal oxides. The use of active materials in conjunction with, i.e. in combination with, the respective molecular sieves can improve the conversion and / or selectivity of the catalyst in certain organic conversion processes. Inert materials preferably function as diluents to control the magnitude of conversion in the process, thereby making it possible to obtain the reaction products economically and regularly without employing other means to regulate the reaction rate. Naturally occurring clays, such as bentonite and kaolin, have often been incorporated into crystalline catalytic materials. These materials, i.e. clays, oxides, etc., function in part as binders for the catalyst. It is desirable to provide catalysts with good crushing strength, because in the field, catalysts are often roughly handled, which tends to break them down into powder-like materials, which can cause problems in the process.
[0036] Naturally occurring clays which may be composited with each of the molecular sieves employed herein include the montmorillonite and kaolin families, including sub-bentonites and kaolins commonly referred to as Dixie, McNamee, Georgia, and Florida clays, or others in which the major mineral component is halloysite, kaolinite, dickite, nacrite, or anauxite. Such clays may be used in the unrefined state as originally mined, or may be first subjected to calcination, acid treatment, or chemical modification.
[0037] In addition to the materials mentioned above, the molecular sieves of the present invention may be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and even ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia. The matrix may be in the form of a cogel. Mixtures of these components may also be used. Preferably, the binder is alumina.
[0038] The relative ratio of zeolite (i.e., molecular sieve) to matrix in each of the individual zeolites making up the coextruded dewaxing catalyst can vary widely. The zeolite content of the zeolite and matrix of the coextrudate can range from about 1 to about 90 weight percent of the composite, more usually from about 2 to about 80 weight percent. The preferred ratio of zeolite / matrix for each zeolite in the coextruded catalyst is 65 / 35 or 80 / 20, based on the total weight of each zeolite.
[0039] The relative ratio of the first zeolite to the second zeolite can also vary. The ratio of the first zeolite to the second zeolite can be at least about 25:75, or at least about 50:50, or at least about 65:35, or at least about 75:25, or at least about 85:15, or at least about 90:10. The ratio of the first zeolite to the second zeolite can also be about 98:2 or less, or about 95:5 or less, or about 90:10 or less, or about 85:15 or less, or about 75:25 or less. In the preferred combination of 10MR / matrix or 10MR and 12MR / matrix, the molecular sieves are included in a ratio of at least about 75:25.
[0040] The relative proportions of each zeolite and matrix material in the coextruded dewaxing catalyst can also vary widely. The weight ratio of the first zeolite to the second zeolite to the matrix in the coextruded dewaxing catalyst can be 15 / 65 / 20, or 40 / 40 / 20, or 70 / 15 / 15, based on the total weight of the dewaxing catalyst.
[0041] The amount of metal in the dewaxing catalyst can be at least 0.1 wt.%, e.g., at least 0.15 wt.%, at least 0.2 wt.%, at least 0.25 wt.%, at least 0.3 wt.%, or at least 0.5 wt.%, based on the weight of the catalyst. The amount of metal in the catalyst can additionally or alternatively be 20 wt.% or less, e.g., 10 wt.% or less, 5 wt.% or less, 2.5 wt.% or less, or 1 wt.% or less, based on the weight of the catalyst. In embodiments where the metal is Pt, Pd, other Group 8 noble metals, or combinations thereof, the amount of metal can be 0.1-5 wt.%, e.g., 0.1-2 wt.%, 0.25-1.8 wt.%, or 0.4-1.5 wt.%. In embodiments where the metals are a combination of non-noble Group 8 and Group 6 metals, the total amount of metals can be from 0.5% to 25% by weight, such as from 2% to 20% by weight, or from 5% to 18% by weight.
[0042] In one or more embodiments, the catalyst for trim dewaxing of distillate boiling range feeds comprises a co-extrudate of two different 10-ring zeolites and a non-precious metal component comprising a first metal and a second metal, wherein the first metal is selected from the group consisting of nickel, cobalt, and mixtures thereof, and the second metal is selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof.
[0043] In another embodiment, the catalyst for trim dewaxing of a distillate boiling range feed includes a co-extrudate of a 10-ring zeolite and a 12-ring zeolite and a non-precious metal component including a first metal and a second metal, wherein the first metal is selected from the group consisting of nickel, cobalt, and mixtures thereof, preferably nickel or cobalt, and the second metal is selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof, preferably molybdenum.
[0044] In one or more embodiments, the catalyst for trim dewaxing of distillate boiling range feeds includes a co-extrudate of two different 10-ring zeolites and a precious metal selected from the group consisting of palladium, platinum, and mixtures thereof, preferably platinum.
[0045] In another embodiment, the catalyst for trim dewaxing of distillate boiling range feeds includes a co-extrudate of a 10-ring zeolite and a 12-ring zeolite and a precious metal selected from the group consisting of palladium, platinum, and mixtures thereof.
[0046] In one or more embodiments, the catalyst for trim dewaxing distillate boiling feeds includes co-extrudates of different 10 MR ZSM-11 and ZSM-48, or 10 MR and 12 MR ZSM-23 and ZSM-48. In some embodiments, the non-noble metals are cobalt and molybdenum, or preferably nickel and molybdenum.
[0047] In one or more embodiments, the catalyst for trim dewaxing distillate boiling feeds includes co-extrudates of different 10 MR of ZSM-11 and ZSM-48, or 10 MR and 12 MR of ZSM-23 and ZSM-48. In some embodiments, the precious metal is palladium, preferably platinum.
[0048] Method for Making a Dewaxing Catalyst The method of making or forming a dewaxing catalyst includes multiple steps. The method includes forming a mixture of zeolites including a first zeolite, a second zeolite, and optionally a binder or support material. The zeolite can be combined with a binder in any convenient manner. In one embodiment, a bound dewaxing catalyst can be made by starting with both the zeolite and binder as powders, combining the powders by adding water to form a paste mixture, and then extruding the mixture into a bound catalyst of the desired size. Optionally, an extrusion agent / aid can be further used to improve the flowability of the zeolite and binder mixture for extrusion.
[0049] In another embodiment, the mixture of zeolites can be kneaded (with or without additional water) in a Muller or other mixing device to form an extrudable paste. The extrudable paste can be extruded (with or without an extrusion aid) to form extrudates. The extrudates can be dried at a temperature of about 80° C. to about 200° C. to form dried extrudates. The dried extrudates can be treated (using one or more methods described below) to form metal-containing extrudates, for example, by adding hydrogenation components using a solution containing a source of metal ions from Group 6 of the Periodic Table, a source of metal ions from Group 10 of the Periodic Table, and optionally a dispersing agent. The metal-containing extrudates can be dried at a temperature of about 80° C. to about 200° C. to form the dewaxing catalyst.
[0050] For example, in the case of platinum, such components can be impregnated into or onto the respective molecular sieves by treating the material with platinum metal-containing ions. Suitable platinum compounds for this purpose include a variety of compounds including chloroplatinic acid, platinous chloride, and platinum amine complexes. Combinations of metals and methods for their introduction can also be used.
[0051] In one or more embodiments, the zeolite mixture may include water and / or the solids content of the extrudable paste is about 45% to 55% by weight.
[0052] Optionally, the zeolite mixture may include an extrusion aid, which may comprise, consist of, or be selected from the group consisting of tetraethylammonium hydroxide, citric acid, sodium hydroxide, nitric acid, methocel™, and mixtures thereof.
[0053] The metal hydrogenation components may be added to the additional catalyst in any convenient manner: such components may be exchanged into the composition, impregnated therein, or physically intimately mixed therewith.
[0054] One method for adding metal hydrogenation components can be by incipient wetness. For example, the zeolite and binder are combined and then the combined zeolite and binder are extruded into catalyst particles. These catalyst particles are then exposed to a solution containing a suitable metal precursor. Alternatively, metals can be added to the catalyst by ion exchange, where the metal precursor is added to a mixture of zeolites (or zeolite and binder) prior to extrusion.
[0055] In some embodiments, the metal hydrogenation components can be added to the catalyst particles by impregnation techniques. In some cases, when the catalyst particles are impregnated with a base metal salt, the catalyst particles may be impregnated using a solution that may further include a dispersant / adjuvant.
[0056] Impregnation, such as incipient wetness and / or ion exchange in solution, is a commonly used technique for introducing metals into catalysts including supports. In impregnation, the support is typically exposed to a solution containing the salt of the metal for impregnation. There are many factors that can affect the dispersion of the metal salt during impregnation, such as the concentration of the salt, the pH of the salt solution, the point of zero charge of the support material, but this does not exclude other factors that may also be important during incipient wetness and / or ion exchange impregnation. In some cases, multiple exposure steps can be performed to achieve the desired metal loading on the catalyst. After impregnation of the support with the aqueous metal salt solution, the support can be dried to remove excess water. The drying can be performed under any convenient atmosphere, such as air, at a temperature of about 80° C. to about 200° C. In some cases, but preferably, if a dispersant / auxiliary is included in the impregnation solution, the catalyst particles are left uncalcined and subsequently sulfided. Alternatively, after impregnation, the catalyst particles can be calcined at a temperature between about 250°C and about 550°C.
[0057] In addition to the water-soluble metal salt, the impregnation solution may contain one or more dispersing agents / auxiliaries. Dispersing agents are used to meek the isolated metals in the dewaxing catalyst. The dispersing agents / auxiliaries may include or be organic compounds containing 2 to 10 carbons and may have a carbon to oxygen atom ratio of about 2 to about 0.6. In some cases, the dispersing agents / auxiliaries may include or be carboxylic acids. Examples of suitable dispersing agents / auxiliaries include: glycols (e.g., ethylene glycol) and carboxylic acids, such as citric acid and gluconic acid. In some cases, the dispersing agents / auxiliaries may include or be amines or other nitrogen-containing compounds, such as nitrilotriacetic acid. Without being bound to any particular theory, it is believed that the dispersing agents / auxiliaries may be removed from the catalyst during the heating and / or calcination steps performed after the impregnation process to form the metal oxides from the metal salts.
[0058] The amount of dispersant / auxiliary in the impregnation solution may be selected based on the amount of metal in the solution. In some embodiments, the molar ratio of dispersant / auxiliary to total metal in the solution may be from about 0.1 to about 5.0, e.g., from about 0.1 to about 2.0, from about 0.1 to about 1.0, from about 0.2 to about 5.0, from about 0.2 to about 2.0, from about 0.2 to about 1.0, from about 0.3 to about 5.0, from about 0.3 to about 2.0, from about 0.3 to about 1.0, from about 0.4 to about 5.0, from about 0.4 to about 2.0, or from about 0.4 to about 1.0, or about 2. Additionally or alternatively, in those embodiments in which a non-noble metal from Group 8 of the Periodic Table is present in the impregnation solution, the molar ratio of dispersant / adjuvant to non-noble metal from Group 8 of the Periodic Table can be from about 0.5 to about 10, e.g., from about 0.5 to about 5.0, from about 0.5 to about 3.0, from about 1.0 to about 10, from about 1.0 to about 5.0, or from about 1.0 to about 3.0.
[0059] After forming a dewaxing catalyst containing supported non-precious base metals and precious base metals, the base metals are sulfided and then used to form a sulfided base metal catalyst. The sulfiding reaction of the metals can be carried out in any convenient manner, such as a gas phase sulfiding process and / or a liquid phase sulfiding process. The sulfiding reaction can generally be carried out by contacting the catalyst containing metal oxides with a sulfur-containing compound, such as elemental sulfur, hydrogen sulfide, and / or polysulfides. Hydrogen sulfide can be a convenient sulfiding agent for the gas phase sulfiding reaction and can be incorporated in an amount of about 0.1% to 10% by weight into the gas phase sulfiding atmosphere containing hydrogen. The sulfiding reaction can additionally or alternatively be carried out in the liquid phase using a combination of hydrogen and a hydrocarbon stream spiked with a polysulfide, such as dimethyl disulfide. The sulfiding reaction can be carried out at any convenient sulfiding temperature, such as 150° C. to 500° C. The sulfurization reaction can be carried out at any convenient sulfurization pressure, for example, from 100 psig to 1000 psig or more. The sulfurization time can vary depending on the sulfurization conditions, but sulfurization times of 1 hour to 72 hours are often suitable. The catalyst may be further steamed, if desired, prior to use.
[0060] Catalytic Dewaxing Process The catalytic dewaxing process of the present invention for trim dewaxing of a distillate boiling range feed comprises contacting at least a portion of the distillate boiling range feed with any of the dewaxing catalysts of the present invention under effective processing conditions.
[0061] In the process, the process conditions in the catalytic dewaxing zone include a temperature of 200° C. to 450° C., for example, 270° C. to 400° C. In some cases, the hydrogen partial pressure is 1.8 MPa g to 35 MPa g (250 psig to 5000 psig), for example, 4.9 MPa g to 20.9 MPa g, and the hydrogen treat gas velocity is 34 Nm 3 / m 3 (about 200SCF / B)~1700Nm 3 / m 3(approximately 10,000 scf / B), for example, 170 Nm 3 / m 3 (about 1000SCF / B)~850Nm 3 / m 3 (about 5000 SCF / B). In yet another embodiment, the following conditions may be included: temperature in the range of 600° F. (343° C.) to 815° F. (435° C.), hydrogen partial pressure in the range of 500 psig to 3000 psig (3.5 MPag to 20.9 MPag), and hydrogen treat gas velocity in the range of 200 Nm 3 / m 3 ~1020Nm 3 / m 3 (about 1200 SCF / B to about 6000 SCF / B). For example, these latter conditions would be appropriate if the dewaxing stage were to be operated under sour conditions. The liquid hourly space velocity (LHSV) would be 0.2 h -1 ~10h -1 , for example 0.5h -1 ~5h -1 , and / or 1h -1 ~4h -1 It can be said that:
[0062] Additionally or alternatively, the conditions for dewaxing can be selected based on the reaction conditions of the preceding stage, e.g., hydrocracking and / or hydrotreating conditions. Such conditions can be further modified by utilizing a temperature quench between the preceding catalyst bed and the bed for the dewaxing catalyst. Instead of operating the dewaxing process at a temperature corresponding to the outlet temperature of the preceding catalyst bed, a temperature quench can be utilized to lower the temperature for the hydrocarbon stream at the beginning of the dewaxing catalyst bed. As an option, the temperature quench can be utilized to have a temperature at the beginning of the dewaxing catalyst bed that is the same as the outlet temperature of the preceding catalyst bed. Yet another option is to utilize a temperature quench to have the temperature at the beginning of the wax catalyst bed at least 10°F (6°C) lower than the preceding catalyst bed, e.g., at least 20°F (11°C) lower, at least 30°F (16°C) lower, or at least 40°F (21°C) lower, and in some cases up to 150°F (90°C) lower.
[0063] In one embodiment, the dewaxing catalyst of the present invention may be included in the same stage and / or in the same reactor and / or in the same layer as a hydrotreating catalyst. Such dewaxing catalyst may be mixed with a hydrotreating catalyst and / or such dewaxing catalyst may be downstream (either in the same layer or in a separate layer) from at least a portion of the hydrotreating catalyst or from substantially all of the hydrotreating catalyst.
[0064] In other embodiments, such a dewaxing catalyst may be located in a layer downstream of any hydrocracking catalyst stage and / or downstream of any hydrocracking catalyst present in a stage.
[0065] Hydrotreating a distillate boiling range feed to a dewaxing process allows dewaxing to occur on molecules that have already been hydrotreated or hydrocracked to remove a significant proportion of organic sulfur- and nitrogen-containing species. Such hydrotreating of a distillate feed reduces poisoning of the dewaxing catalyst and extends its cycle life. The dewaxing catalyst may be located in the same reactor as at least a portion of the hydrocracking catalyst in a stage. Alternatively, the effluent from a reactor containing a hydrocracking catalyst can be fed, possibly after gas-liquid separation, to another stage or reactor containing a dewaxing catalyst. In yet another embodiment, the dewaxing catalyst can be used in a catalyst layer at least one layer before (i.e., upstream in the process flow) the hydrotreating and / or hydrocracking catalyst.
[0066] In yet another alternative, the dewaxing catalyst in the final reaction stage may be mixed with other types of catalysts, such as hydrotreating catalysts, in at least one layer in the reactor. In yet another alternative, the hydrocracking and dewaxing catalysts may be coextruded with a single binder to form a mixed functionality catalyst.
[0067] Hydrotreating Process Typically, hydrotreating can be used to reduce the sulfur, nitrogen, and aromatics content of the feed. Catalysts used for hydrotreating include conventional hydrotreating catalysts, such as those containing at least one non-noble metal (columns 8-10 of the periodic table), such as Fe, Co, and / or Ni, such as at least Co and / or Ni, and at least one group 6 metal, such as Mo and / or W. Such hydrotreating catalysts include transition metal sulfides, optionally impregnated or dispersed on a refractory support / carrier, such as alumina and / or silica. The support / carrier itself typically has little or no significant or measurable catalytic activity. Substantially carrier-free or support-free catalysts (commonly referred to as bulk catalysts) generally have higher volumetric activity than their supported counterparts.
[0068] Hydroprocessing may be advantageously carried out in the presence of hydrogen. Thus, a hydrogen stream may be fed or injected into the vessel / reaction zone / hydroprocessing zone in which the hydroprocessing catalyst is located. Hydrogen (contained in a hydrogen "treat gas") may be supplied to the reaction zone. The treat gas may be pure hydrogen or may be a hydrogen-containing gas containing sufficient hydrogen for the intended reaction and possibly one or more other gases (e.g., nitrogen and / or light hydrocarbons such as methane, which ideally should not interfere with or adversely affect either the reaction or the products of the reaction). Impurities such as H2S and NH3 are undesirable and typically are removed from the treat gas prior to passing to the reactor. In those embodiments in which the treat gas stream introduced into the reaction stage contains components other than hydrogen, the treat gas may contain at least 50% by volume, e.g., at least 75% by volume, at least 90% by volume, at least 95% by volume, or at least 99% by volume H2.
[0069] Hydrogen is supplied at 100 SCF / B (standard cubic feet of hydrogen per barrel of feedstock) (approximately 17 Nm 3 / m 3 ) ~ Approx. 1500SCF / B (Approx. 250Nm 3 / m 3 In certain embodiments, hydrogen can be supplied at a rate of 200 SCF / B (about 34 Nm 3 / m 3 ) ~ 1200SCF / B (approx. 200Nm 3 / m 3 Hydrogen may be fed co-currently to the feedstock entering the hydroprocessing reactor / reaction zone and / or fed separately to the hydroprocessing zone through a separate gas conduit.
[0070] The hydrotreating conditions may include the following: temperature, 200°C to 450°C, for example, 315°C to 425°C; pressure, 250 psig (about 1.8 MPag) to 5000 psig (about 35 MPag), for example, 300 psig (about 2.1 MPag) to 3000 psig (about 20.9 MPag); liquid hourly space velocity (LHSV), 0.1 hr -1 ~10hr -1 ; and the hydrogen treatment rate is 200 scf / B (approximately 34 Nm 3 / m 3 ) ~ 10000scf / B (approx. 1700Nm 3 / m 3 ), for example, 500scf / B (approx. 85Nm 3 / m 3 ) ~ 10000scf / B (approx. 1700Nm 3 / m 3 ).
[0071] The present invention will now be described in more detail with reference to the following examples and the accompanying drawings, in which the benefits of using two different 10MR catalysts, or 10MR and 12MR skeletal catalysts, are shown for the production of diesel boiling range products. EXAMPLES
[0072] Example 1: 3.4% Ni / 14% Mo, 65 / 35 ZSM-11 / Al2O3 (MEL) 65 parts ZSM-11 crystals were mixed with 35 parts alumina (Versal 300™, available from Honeywell UOP) in a muller. Sufficient water was added to make an extrudable paste on a 6″ extruder, with total solids ranging from 49-53%. The ZSM-11, alumina, and water mixture was extruded (extruded) into 1 / 16″ cylinders and then dried at 121° C. in a conveyor convection oven for several hours. The dried extrudates were pre-calcined at 538° C. in nitrogen to decompose and remove the organic template. The mixture was then cooled to 37° C. for 1 hour. The pre-calcined extrudates were humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions, and then dried at 121°C for at least 4 hours. They were then calcined in air at 538°C. To a minimum amount of water, citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target a final loading of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets, and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0073] Example 2: 3.4% Ni / 14% Mo, 80 / 20 ZSM-48 / SiO2 (MRE) 80 parts ZSM-48 crystals were mixed in a muller with 3 parts NaOH followed by 10 parts solid silica (Ultrasil™, available from Evonik) and 10 parts colloidal silica (Ludox™ HS-40, available from WR Grace). Enough water was added in the range of 50-60% of the total solids to make an extrudable paste on a 1" extruder. The ZSM-48, silica, and water mixture was extruded into 1 / 16" pillars and then dried at 121°C in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538°C in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions, and then dried at 121°C for at least 4 hours. They were then calcined in air at 538°C. To a minimum amount of water, citric acid (citrate / Ni=2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target a final loading of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets, and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0074] Example 3: 3.4% Ni / 14% Mo, 70 / 15 / 15 ZSM-48 / ZSM-11 / Al2O3 (MEL / MRE) 70 parts ZSM-48 crystals were mixed in a muller with 2 parts tetraethylammonium hydroxide followed by 15 parts ZSM-11 and 15 parts solid alumina (Versal 300™). Enough water was added to make an extrudable paste on a 1″ extruder in the range of 49-53% of the total solids. The ZSM-48, ZSM-11, alumina, and water mixture was extruded into 1 / 16″ pillars and then dried at 121° C. in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538° C. in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions and then dried at 121° C. for at least 4 hours. It was then calcined in air at 538°C. To a minimum amount of water, citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target a final loading of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0075] Example 4: 3.4%Ni / 14%Mo, 65 / 35 ZSM-48 / Al2O3, + 3.4%Ni / 14%Mo, 65 / 35 ZSM-11 / Al2O3 (MEL+MRE) 65 parts ZSM-48 crystals were mixed with 35 parts alumina (Catapal™ 200, available from Sasol North America) in a muller. Enough water was added to make an extrudable paste on a 6″ extruder, ranging from 49-53% of the total solids. The ZSM-48, alumina, and water mixture was extruded into 1 / 16″ pillars and then dried at 121° C. in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538° C. in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions and then dried at 121° C. for at least 4 hours. It was then calcined in air at 538°C followed by treatment with water steam at 371°C. Citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate followed by ammonium heptamolybdate tetrahydrate were added to a minimum amount of water to target a final loading of 3.4% Ni and 14.0% Mo, respectively, by weight. The solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets and slowly added to the pellets which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C. A physical mixture was prepared by combining 79 parts of this ZSM-48 material with 21 parts of the ZSM-11 material described above in Example 1.
[0076] Example 5: 3.4% Ni / 14% Mo, 80 / 20 ZSM-23 / Al2O3 (MTT) 80 parts ZSM-23 crystals were mixed with 20 parts alumina (Versal 300™) in a muller. Enough water was added to make an extrudable paste on a 6″ extruder, ranging from 49-53% of the total solids. The ZSM-23, alumina, and water mixture was extruded into 1 / 16″ pillars and then dried at 121° C. in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538° C. in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions before drying at 121° C. for at least 4 hours. They were then calcined at 538° C. in air. To a minimum amount of water, citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target final loadings of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0077] Example 6: 3.4%Ni / 14%Mo, 65 / 35 ZSM-12 / Al2O3 (MTW) 65 parts ZSM-23 crystals were mixed with 2 parts tetraethylammonium hydroxide and 15 parts alumina (Versal 300™) in a muller. Enough water was added to make an extrudable paste on a 6″ extruder, ranging from 49-53% of the total solids. The ZSM-12, alumina, and water mixture was extruded into 1 / 16″ pillars and then dried at 121° C. in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538° C. in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions before drying at 121° C. for at least 4 hours. They were then calcined at 538° C. in air. To a minimum amount of water, citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target final loadings of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0078] Example 7: 3.4% Ni / 14% Mo, 40 / 40 / 20 ZSM-48 / ZSM-23 / Al2O3 (40 / 40 MRE / MTT) 40 parts ZSM-48 crystals were mixed with 40 parts ZSM-23, then 2 parts tetraethylammonium hydroxide and 15 parts alumina (Versal 300™) were added to the muller. Enough water was added in the range of 49-55% of the total solids to make an extrudable paste on a 6″ extruder. The ZSM-48, ZSM-23, alumina, and water mixture was extruded into 1 / 16″ pillars and then dried at 121°C in a conveyor convection oven for several hours. The dried extrudates were precalcined at 538°C in nitrogen to decompose and remove the organic template. The precalcined extrudates were then humidified with 2 cc / g / min saturated air for 1 hour under ambient conditions. After humidification, the extrudates were ion-exchanged with 1N ammonium nitrate to remove sodium. The extrudates were then washed with deionized water to remove residual nitrate ions and then dried at 121°C for at least 4 hours. It was then calcined in air at 538°C. To a minimum amount of water, citric acid (citric acid / Ni: molar ratio 2) and sufficient nickel carbonate hydroxide tetrahydrate, followed by ammonium heptamolybdate tetrahydrate, were added to target a final loading of 3.4% Ni and 14.0% Mo, respectively, by weight. This solution was then diluted to a total volume equal to the measured water pore volume of the extruded pellets and slowly added to the pellets, which were then tumbled to ensure mixing. The impregnated pellets were dried at 121°C.
[0079] Example 8: 1.7%Ni / 7.0%Mo, 65 / 15 / 20 ZSM-48 / ZSM-23 / Al2O3 (1 / 2 NiMo, 40 / 40 MRE / MTT) Example 8 was prepared in an identical manner to Example 7, except that the final loadings, by weight, were 1.7% Ni and 7.0% Mo, respectively.
[0080] Example 9: 3.4% Ni / 14% Mo, 65 / 15 / 20 ZSM-48 / ZSM-23 / Al2O3 (65 / 15 MRE / MTT) Example 9 was prepared in the same manner as Example 7 except that 65 parts ZSM-48 crystals and 15 parts ZSM-23 crystals were used.
[0081] Example 10: 3.4% Ni / 14% Mo, 15 / 65 / 20 ZSM-48 / ZSM-23 / Al2O3 (15 / 65 MRE / MTT) Example 10 was prepared in the same manner as Example 7, except that 15 parts ZSM-48 crystals and 65 parts ZSM-23 crystals were used.
[0082] Example 11: 3.4% Ni / 14% Mo, 40 / 40 / 20 ZSM-48 / ZSM-12 / Al2O3 (40 / 40 MRE / MTW) Example 11 was prepared in the same manner as Example 7, except that 40 parts ZSM-48 crystals and 40 parts ZSM-12 crystals were used.
[0083] Example 12: Performance evaluation The properties of the feeds used in the performance evaluation of the catalysts in the above examples are shown in Table 1.
[0084] [Table 1]
[0085] The catalysts were arranged in a typical trim dewaxing configuration with a first layer of hydrotreating catalyst at 80% (v / v) (volume of first layer catalyst / total volume of first and second layers), followed by a second layer of dewaxing catalyst at 20% (v / v). The reactor was configured for downflow operation and off-gas was monitored with a wet test meter and GC. All liquid reaction products were also collected and tested for simulated distillation and residual organic sulfur and nitrogen. All material balances were close to 100±3%. All catalysts were sulfided in the unit using 3% sulfur-laden LVGO (light vacuum gas oil) before exposure to the actual feed. Testing was completed using lined out catalyst, but conditions for both feeds are shown in Tables 2-4. Cloud points were averaged over each condition. In all runs using the conditions from Table 2, reaction product nitrogen values were undetectable in all balances.
[0086] Condition set 1 for testing the temperature dependence of cloud point reduction in feed 1 is shown in Table 2.
[0087] [Table 2]
[0088] Condition set 2 for testing the temperature dependence of cloud point reduction in feed 2 is shown in Table 3.
[0089] [Table 3]
[0090] The results of the performance evaluation of the catalysts of the examples are shown in FIGS.
[0091] Figure 1 shows the cloud point reduction performance of materials containing MEL and MRE (10MR) backbones over a range of temperatures under condition set 1 using feed 1. Specifically, Figure 1 shows the performance of materials containing MEL and MRE backbones alone as well as their physical mixtures (MEL+MRE) and co-extruded forms (MEL / MRE). As can be seen, the co-extruded material (MEL / MRE) showed significantly higher activity in terms of cloud point reduction with feed 1 than the physically mixed sample (MEL+MRE), especially at higher temperatures. The co-extruded material also showed better performance than the individual materials containing the MEM and MRE backbones alone.
[0092] A common concern associated with highly active materials is their tendency to crack diesel range molecules into light ends, resulting in diesel losses that are economically undesirable. Figure 2 shows the diesel losses vs. cloud point reduction for Feed 1 under Condition Set 1 for materials containing MEL and MRE backbones. It becomes apparent from Figure 2 that the co-extruded material containing MEL / MRE backbones not only exhibits high activity over a temperature window, but also has improved diesel yields compared to other materials containing MEL or MRE backbones alone, or physical mixtures of MEL+MRE backbones.
[0093] FIG. 3 shows the cloud point reduction performance of materials containing MTT and MRE(10MR) backbones over a range of temperatures under condition set 2 with feed product 2. Specifically, coextruded materials containing MTT and MRE backbones (10MR) were tested over a range of MRE / MTT ratios. As can be seen from FIG. 3, the increased activity of the coextruded materials is not limited to the MEL and MRE(10MR) backbones or feed product 1. The cloud point reduction performance can be tuned by selectively varying the catalyst ratio. In this study, 65 / 15 and 40 / 40 MRE / MTT showed higher activity than either materials containing MTT alone or MRE alone, while materials containing more of the less active MTT component were less active than MRE alone.
[0094] Figure 4 shows the diesel losses vs. cloud point reduction for Feed 2 under Condition Set 2 for materials containing MTT and MRE(10MR) backbones. As with the co-extruded materials containing MEL / MRE(10MR) backbones, all of the materials containing MRE / MTT backbones show lower diesel losses and therefore improved selectivity for isomerization in cracking compared to the parent materials. This again shows the superiority of the co-extruded materials over the single MEL backbone material or the single MRE backbone material or the single MTT(10MR) backbone material.
[0095] In addition to varying frameworks and feeds, this technique of co-extruding zeolites can also be combined with varying metal content. Figure 5 shows the cloud point reduction performance of materials containing MTT and MRE(10MR) frameworks with different metal loadings over a temperature range under condition set 2 with feed 2. Figure 6 shows diesel loss vs. cloud point reduction for feed 2 under condition set 2 for materials containing MTT and MRE(10MR) frameworks with different metal loadings. Figures 5 and 6 show the activity improvement for co-extruded 40MRE / 40MTT material with a 50% reduction in Ni / Mo metal loading (from 3.4%Ni / 14%Mo to 1.7%Ni / 7.0%Mo by weight, respectively). As can be seen from these Figures 5 and 6, the improved activity and selectivity for the MTT and MRE(10MR) scaffolds with 50% metal loading is nearly equivalent to the same MTT and MRE(10MR) scaffolds with 100% metal catalyst, which is an improvement over either the materials containing a single MTT scaffold or a single MRE scaffold.
[0096] FIG. 7 shows the cloud point reduction performance of materials containing MTW (12MR) and MRE (10MR) backbones over a temperature range under condition set 2 for feed 2. FIG. 8 shows diesel loss vs. cloud point reduction for feed 2 under condition set 2 for materials containing MTW (12MR) and MRE (10MR) backbones. In the case of materials containing a combination of MTW and MRE backbones, comparable activity was observed between materials containing MTW (12MR) backbones alone and co-extrusions of MRE / MTW materials (FIG. 7). However, the co-extruded material showed a 1% improvement in diesel yield compared to MTW alone (FIG. 8). This shows the advantage of co-extrusion materials containing multiple backbones instead of using a single backbone.
[0097] Without wishing to be bound by any theory, it is believed that preparing the dewaxing catalyst by co-extruding different framework materials (and optionally binders) results in more intimate mixing and improved framework material homogeneity, thereby improving access to acid sites within the catalyst and exhibiting accelerated cloud point reduction without the undesirable increase in diesel losses during the dewaxing process.
[0098] All priority documents, patents, publications, and patent applications, test procedures (e.g., ASTM methods), and other documents cited herein are hereby fully incorporated by reference to the extent such disclosures are consistent with the present invention and to the extent such incorporation is permitted in any jurisdiction.
[0099] When numerical lower and upper limits are listed herein, ranges from any lower limit to any upper limit are contemplated.
[0100] While particular embodiments have been described to illustrate the invention, it is to be understood that various other modifications will be apparent and readily made by those skilled in the art without departing from the spirit and scope of the invention. Accordingly, it is not intended that the scope of the claims appended hereto be limited to the examples and descriptions mentioned herein, but rather that the claims should be construed to encompass all patentable novel features contained in the present invention, including all features that would be treated as equivalents by those skilled in the art to which the invention pertains.
Claims
1. 1. A process for trim dewaxing a distillate boiling range feed comprising: contacting at least a portion of the distillate boiling range feed with a dewaxing catalyst under effective dewaxing conditions to form a diesel boiling range product, said dewaxing catalyst comprising: (a) a co-extrudate of two different 10-ring zeolites; or (b) coextrudates of 10-ring zeolites and 12-ring zeolites; and (c) a non-precious metal component comprising a first metal and a second metal, said first metal being selected from the group consisting of nickel, cobalt, and mixtures thereof; and said second metal being selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof. The process includes:
2. 2. The process of claim 1, wherein the 10-ring zeolite has a framework type selected from the group consisting of EUO, MEL, MFI, MFS, MRE, MTT, MWW, MWW, NES, TON, and mixtures thereof.
3. 3. The process of any of claims 1 to 2, wherein the 10-ring zeolite is selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, ZSM-23, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof.
4. The 12-membered ring zeolite is * 4. The process of any of claims 1 to 3, having a backbone type selected from the group consisting of BEA, BEC, EMT, FAU, LTL, MEI, MOR, MOZ, MTW, MSE, OFF, and mixtures thereof.
5. 5. The process of any of claims 1 to 4, wherein the 12-ring zeolite is selected from the group consisting of beta, ZSM-2, ZSM-3, ZSM-20, Y, US-Y, L, ZSM-18, mordenite, ZSM-10, ZSM-12, MCM-68, offretite, and mixtures thereof.
6. The process of any one of claims 1 to 5, wherein the coextrudates of two different 10-ring zeolites are ZSM-11 and ZSM-48, or ZSM-11 and ZSM-23.
7. 7. The process of any one of claims 1 to 6, wherein the coextrudate of the 10-ring zeolite and the 12-ring zeolite is ZSM-48 and ZSM-12.
8. 1. A process for trim dewaxing a distillate boiling range feed comprising contacting at least a portion of the distillate boiling range feed with a dewaxing catalyst under effective dewaxing conditions to form diesel boiling range products, said dewaxing catalyst comprising: (a) a co-extrudate of two different zeolites, wherein the zeolites are independently selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof; or (b) co-extrudates of a 10-ring zeolite with a 12-ring zeolite, wherein the 10-ring zeolite is selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, ZSM-23, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof; and the 12-ring zeolite is selected from the group consisting of beta, ZSM-2, ZSM-3, ZSM-20, Y, US-Y, L, ZSM-18, mordenite, ZSM-10, ZSM-12, MCM-68, offretite, and mixtures thereof; and (c) a precious metal component selected from the group consisting of palladium, platinum, and mixtures thereof; The process includes:
9. The process of any of claims 1 to 8, wherein the dewaxing catalyst further comprises a binder, the binder optionally comprising alumina, silica, silica alumina, zirconia, or titania, and mixtures thereof.
10. 10. The process of any of claims 1 to 9, further comprising contacting a portion of the distillate boiling range feed with a hydrotreating catalyst under hydrotreating conditions.
11. 11. The process of claim 10, wherein the hydrotreating catalyst comprises at least one of cobalt, nickel, molybdenum, platinum, tungsten, alumina, silica, silica alumina, zeolites, and molecular sieves.
12. 11. The process of claim 10, wherein the hydrotreating catalyst and the dewaxing catalyst are disposed in contact with the fluid in a stacked catalyst layer, or intermingled in a mixed catalyst layer, or a combination thereof.
13. The process of any of claims 1 to 12, wherein the effective dewaxing conditions comprise a temperature of at least about 300°C, such as at least about 325°C, such as at least about 350°C, or at least about 400°C.
14. 1. A method of forming a dewaxing catalyst, the method comprising: (a) forming a mixture comprising a first zeolite, a second zeolite, and a binder; (b) kneading the mixture to form an extrudable paste; (c) extruding the extrudable paste to form an extrudate; and (c) drying the extrudate at a temperature of about 80° C. to about 200° C. to form a dried extrudate; (d) impregnating the dried extrudates with a solution comprising a source of metal ions from Group 6 of the Periodic Table, a source of metal ions from Group 10 of the Periodic Table, and, optionally, a dispersing agent to form metal-containing extrudates; and (e) drying the metal-containing extrudates at a temperature of from about 80° C. to about 200° C. to form a dewaxing catalyst; A method comprising:
15. The method of claim 14, wherein the mixture further comprises water and the solids content of the extrudable paste is about 45% to 55% by weight.
16. 16. The method of claim 14 or 15, wherein the mixture further comprises an extrusion aid, the extrusion aid being selected from the group consisting of tetraethylammonium hydroxide, citric acid, sodium hydroxide, nitric acid, methocel™, and mixtures thereof.
17. The process of any one of claims 14 to 16, wherein the dewaxing catalyst is sulfided.
18. The process of claims 14-16, wherein the dewaxing catalyst is exchanged with a source of ammonium ions, washed with water, dried and calcined.
19. 1. A catalyst system for trim dewaxing a distillate boiling range feed comprising: (a) a co-extrudate of two different 10-ring zeolites; or (b) coextrudates of 10-ring zeolites and 12-ring zeolites; and (c) a non-precious metal component comprising a first metal and a second metal, said first metal being selected from the group consisting of nickel, cobalt, and mixtures thereof; and said second metal being selected from the group consisting of chromium, molybdenum, tungsten, and mixtures thereof. A catalyst system comprising:
20. 1. A catalyst system for trim dewaxing a distillate boiling range feed comprising: (a) a co-extrudate of two different zeolites, wherein the zeolites are independently selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof; or (b) co-extrudates of a 10-ring zeolite with a 12-ring zeolite, wherein the 10-ring zeolite is selected from the group consisting of ZSM-50, EU-1, ZSM-11, ZSM-5, ZSM-57, ZSM-48, ZSM-23, EMM-10, EMM-12, EMM-13, MCM-22, MCM-36, MCM-49, MCM-56, NU-87, ZSM-22, Theta-1, and mixtures thereof; and the 12-ring zeolite is selected from the group consisting of beta, ZSM-2, ZSM-3, ZSM-20, Y, US-Y, L, ZSM-18, mordenite, ZSM-10, ZSM-12, MCM-68, offretite, and mixtures thereof; and (c) a precious metal component selected from the group consisting of palladium, platinum, and mixtures thereof; A catalyst system comprising:
21. 21. The catalyst of claim 19 or claim 20, wherein the coextrudates of two different 10-ring zeolites are coextrudates of ZSM-11 and ZSM-48 or coextrudates of ZSM-23 and ZSM-48.
22. 21. The catalyst of claim 19 or claim 20, wherein the co-extrudate of 10-ring zeolites and 12-ring zeolites is ZSM-48 and ZSM-12.
Citation Information
Patent Citations
Base metal dewaxing catalyst
US20170175011A1
Trim dewaxing of distillate fuel
US20170175015A1
Catalyst composition for use in production of high lubricating oil stock
US4428865A
Dewaxing catalysts and processes
US8298403B2